Gambaran Mekanisme Koping Keluarga Dalam Menghadapi Perilaku Agresif Pada Pasien Skizofrenia - Jumaisah; Sri Wahyuni; Veny Elita (Universitas Bengkulu, 2023)
Schizophrenia is a mental disorder characterized by aggressive behavior that can endanger themselves and others, so it is important for families who care for patients to resolve these problems. This study aims to determine the description of the family's coping mechanisms in dealing with aggressive behavior in Schizophrenic patients. This research is quantitative research with a descriptive design. The sample in this study was 88 people using the Brief Cope questionnaire by Carver which had been tested using 30 samples with 28 questions all declared valid, with the results of r arithmetic (0.366 – 0.826) r table (0.361), and reliable with a value of = 0.764. Most of the respondents have adaptive coping mechanisms as many as 86 people 97.7%. While 2 people 2.3% had maladaptive coping mechanisms in dealing with aggressive behavior in Schizophrenic patients. The family's coping mechanism in dealing with aggressive behavior in Schizophrenic patients is an adaptive coping mechanism.